Transport and kinetics at carbon nanotube-redox enzyme composite modified electrode biosensors - LYONS, MICHAEL EDWARD (Electrochemical Science Group, 2009)
A mathematical model describing transport and kinetics of substrate and redox mediator within chemically modified electrodes comprising of redox enzymes immobilized in dispersed carbon nanotube meshes dispersed on support electrode surfaces is described. Two modes of amperometric detection are subjected to analysis. In the first the current arising from re-oxidation of the reduced mediator at the support electrode is measured, whereas in the second the current arising from reduction of the oxidized mediator at the support surface is determined. Approximate analytical expressions for the substrate reaction flux within the nanotube layer are developed and related to the measured flux at the support surface. The kinetics both of substrate and mediator within the layer are also represented in terms of a kinetic case diagram.
PUBLISHED
Keywords: Amperometric enzyme biosensor modeling; Single wall/ redox enzyme composite; SWNT modified electrodes. Immobilized redox enzyme systems.